2021
DOI: 10.1007/s00701-021-04834-y
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of the cerebrospinal space: comparison of three methods

Abstract: Background Cerebrospinal compliance describes the ability of the cerebrospinal space to buffer changes in volume. Diminished compliance is associated with increased risk of potentially threatening increases in intracranial pressure (ICP) when changes in cerebrospinal volume occur. However, despite various methods of estimation proposed so far, compliance is seldom used in clinical practice. This study aimed to compare three measures of cerebrospinal compliance. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…ICP invasive monitoring in COVID-19 patients would have been unethical and difficult to implement. The B4C device does not provide ICP values; however, it allows a bedside observation and report of the ICP pulse waveform quantitative parameters, a vital sign that is gaining attention in recent years [36,37]. Studies evaluating this ICC device in critically ill patients are few and still ongoing [38]; nevertheless, ICC was adequately assessed in children with hydrocephalus [21] and in experimental studies using this technique [39].…”
Section: Discussionmentioning
confidence: 99%
“…ICP invasive monitoring in COVID-19 patients would have been unethical and difficult to implement. The B4C device does not provide ICP values; however, it allows a bedside observation and report of the ICP pulse waveform quantitative parameters, a vital sign that is gaining attention in recent years [36,37]. Studies evaluating this ICC device in critically ill patients are few and still ongoing [38]; nevertheless, ICC was adequately assessed in children with hydrocephalus [21] and in experimental studies using this technique [39].…”
Section: Discussionmentioning
confidence: 99%
“…ICC is a property of dynamic volumes inside a cavity whose expansion is very limited, indicating the hemostasis amongst them [1]. In addition, ICC may reflect the compensatory changes of vessels (mainly the great intracranial venous sinuses) and the CSF spaces (cisterns, ventricles and subarachnoid), according to ICP elevations [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in recent years the knowledge on the ICP pulse waveform (ICPW) has advanced, as well as its clinical application. ICPW is an early marker of ICC impairment [3,[7][8][9] and is mainly represented by three distinct peaks: P1 (percussion wave), P2 (tidal wave) and P3 (dicrotic wave) [10]. Under physiologic conditions, P1 produced by arterial contraction is the highest peak observed, with P2 reflecting both vascular and ventricular repercussion of pressure pulse spread.…”
Section: Introductionmentioning
confidence: 99%
“…Although not statistically significant, DC patients disclosed higher baseline mean ICP levels and P2/P1 ratio, with a significant decrease in the latter when ICP elevation was induced. Thus, the study demonstrated that P2/P1 ratio may bring additional information for neuromonitoring [3,18] and the effect of DC that not just ameliorated ICP but also increased the intracranial compliance, protecting for further elevations in ICP. This agrees with previous studies using different methodologies [19][20][21].…”
Section: Discussionmentioning
confidence: 73%
“…Likewise, in recent years the knowledge on the ICP pulse waveform (ICPPW) has advanced, as well as its clinical application. ICPPW is an early marker of ICC impairment [3,[7][8][9] and is mainly represented by three distinct peaks, P1 (percussion wave), P2 (tidal wave) and P3 (dicrotic wave) [10].…”
Section: Recently the International Multidisciplinary Consensus Conference On Multimodalitymentioning
confidence: 99%